Critical psychologies and climate change. (December 2021) - Adams, Matthew
Abstract: This article is a review of recent contributions in critical psychology and its close cousins, critical social psychology, critical community psychology and liberation psychology, to understand human response to climate change. It contrasts critical psychology with mainstream psychology in general terms, before introducing a critical psychological perspective on climate change. Central to this perspective is a critique of the framing of individual behaviour change as the problem and solution to climate change in mainstream psychology and a related emphasis on identifying 'barriers' to proenvironmental behaviour. This framework is argued to be reductive, obscuring or downplaying the influence of a range of factors in shaping predominant responses to climate change to date, including social context, discourse, power and affect. Currently, critical psychologies set out to study the relative contribution of these factors to (in)action on climate change. A related concern is how the psychological and emotional impacts of climate change impact unevenly on communities and individuals, depending on place-based, economic, geographic and cultural differences, and give rise to experiences of injustice, inequality and disempowerment. Critical psychology does not assume these to be overriding or inevitable psychological and social responses, however. Critical psychologies also undertake research and inform interventions that highlight the role of collective understanding, activism, empowerment and resistance as the necessary foundations of a genuine shift towards sustainable societies.